Особенности структурной организации миокарда старых крыс с моделью алиментарного ожирения на фоне введения криоконсервированных ядросодержащих клеток кордовой крови - Чернявская, Е.А.; Бабийчук, В.Г. (Український журнал медицини, біології та спорту. 2017. №4,(6): 199–204., 2017)
На сегодняшний день накоплено большое количество данных, свидетельствующих о положительном влиянии препаратов, полученных из кордовой крови, как на разные органы, системы, так и на организм в целом. На экспериментальной модели алиментарного ожирения изучены гистологические особенности состояния тканей и сосудов сердца, проведена гистохимическая оценка состояния коллагеновых и эластических волокон миокарда старых крыс до и после введения криоконсервированных ядросодержащих клеток кордовой крови человека. Установлено, что на фоне введения препарата отмечалась тенденция к нормализации гистологической структуры сердца старых животных с моделью алиментарного ожирения. Положительное влияние сохранялось и в отдаленные сроки экспериментальных исследований. /////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////// Alimentary obesity is a chronic disease with a multifactorial nature, being largely stipulated by a lack of motor activity and hypercaloric nutrition. The obesity increases the morbidity and mortality risks because of various complications and requires an interdisciplinary approach in designing therapeutic and preventive methods. A successful development of cell and tissue therapy is extremely promising for medical purposes. The interest in cord blood, as an alternative source of hematopoietic stem cells, suitable for application in practical medicine, has significantly increased. The use of cord blood is currently indicated in therapy of more than 70 diseases. In this context this research was aimed to evaluate the morphological state of myocardial tissues and blood vessels in experimental old animals with simulated alimentary obesity prior to and after administering the cryopreserved cord blood nucleated cells. Materials and methods. The studies were performed in 24-month-old male rats, which were divided into 3 groups: intact animals, rats with a simulated alimentary obesity, and those with alimentary obesity at the background of cryopreserved cord blood nucleated cells administration. The obesity was simulated according to the V.G. Baranov’s technique by keeping animals on a hypercaloric diet. The frozen-thawed human cord blood nucleated cell preparation was once injected intraperitoneally in a dose of 3×105 of CD34+ cells per kilogram of animal weight. The animals of all the groups were sacrificed via decapitation to days 7 and 30 after administering cord blood nucleated cells. Right after that the animal's heart was cut transversely along the coronary groove, the isolated caudal part (ventricles) was examined histologically and histochemically. Results. During the study a structural organization of cardiac muscle of intact animals was revealed to correspond to the norm. Morphological picture of myocardium in old animals with a simulated alimentary obesity testified to the presence of signs of circulatory disorders, confirmed by vascular congestion and thrombosis, focal cardiosclerosis, diapedetic hemorrhages, myocardial hypertrophy, as well as interstitial and perivascular edema. Large fat drops at the background of small ones were revealed in old animals by means of a specific staining for neutral fats. There was observed a tendency to normalization of histological structure of heart in old animals with simulated alimentary obesity even after cryopreserved cord blood nucleated cell administration. The large vessels were full-blooded with a normal lumen shape and uniformly thickened walls. There were no lymphohistiocytic infiltrates in myocardial tissue, a moderate perivascular edema and cardiosclerosis were revealed around the vessels. When staining histological preparations with oily red, the manifestation rate of fatty degeneration of cardiac muscle decreased. A positive effect was kept even in the more distant periods of experimental research.
Peculiarities of structural organization of myocardium in old rats with simulated alimentary оbesity at the background of cryopreserved cord blood nucleated cell administration
Чернявская Е.А., Бабийчук В. Г. Особенности структурной организации миокарда старых крыс с моделью алиментарного ожирения на фоне введения криоконсервированных ядросодержащих клеток кордовой крови. Український журнал медицини, біології та спорту. 2017. №4,(6): 199–204.
Keywords: алиментарное ожирение; ядросодержащие клетки кордовой крови; кардиомиоциты; кардиосклероз; липидоз